A festschrift for Albert Seay. Essays by his friends and colleagues - Seay, Albert 1916-1984; Grace, Michael D. (Colorado Spring The Colorado Colledge, 1982)
Albert Seay was Professor of Music at Colorado College beginning in 1953 and served as Chair of the Music Department from 1967 until his retirement in 1982. His students and colleagues knew him as a great teacher and scholar who was equally dedicated to both undergraduates and his own internationally acclaimed musicological research. Dr. Seays numerous contributions to the Seay collection include a variety of musicological resources, a large repertoire of piano four-hands and two-piano music, and a collection of unusual woodwind chamber music.Suggestioni teoriche nel Lucidarium di Marchetto da Padova, dai "generi" alla "musica colorata" / Giuseppe MasseraThe manuscript transmission of Hothby's theoretical works / Gilbert ReaneyDe l'attribution a